2017
DOI: 10.1371/journal.pone.0173858
|View full text |Cite
|
Sign up to set email alerts
|

Radiological characteristics of pulmonary cryptococcosis in HIV-infected patients

Abstract: BackgroundCurrent understanding of human immunodeficiency virus (HIV)-associated pulmonary cryptococcosis (PC) is largely based on studies performed about 2 decades ago which reported that the most common findings on chest radiograph were diffuse interstitial infiltrates. Few studies are available regarding the computed tomography (CT) findings. The aim of this study was to characterize chest CT features of HIV-associated PC.MethodsHIV patients with cryptococccal infection and pulmonary abnormalities on Chest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 21 publications
4
18
0
Order By: Relevance
“…An important reason for this discrepancy may be that chest CT scan, which was more sensitive to reveal pulmonary lesions compared with chest radiograph, was routinely performed for patients with cryptococcal antigenemia in our study. As we and others had previously described, the most characteristic radiological features of HIV-associated PC were pulmonary nodules/masses with or without cavitation that may not always be associated with significant respiratory symptoms; clinicians may be unawareness of PC when pulmonary symptoms were not severe (Hu et al, 2013(Hu et al, , 2017Xie et al, 2015). Together, our study suggested that the prevalence of PC in HIV-infected patients may be underestimated.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…An important reason for this discrepancy may be that chest CT scan, which was more sensitive to reveal pulmonary lesions compared with chest radiograph, was routinely performed for patients with cryptococcal antigenemia in our study. As we and others had previously described, the most characteristic radiological features of HIV-associated PC were pulmonary nodules/masses with or without cavitation that may not always be associated with significant respiratory symptoms; clinicians may be unawareness of PC when pulmonary symptoms were not severe (Hu et al, 2013(Hu et al, , 2017Xie et al, 2015). Together, our study suggested that the prevalence of PC in HIV-infected patients may be underestimated.…”
Section: Discussionsupporting
confidence: 64%
“…Here, the characteristic radiographic features were pulmonary nodules/masses with or without cavitation, as we and others found that those lesions were the most common radiological features of PC in immunocompromised HIV-infected patients (Hu et al, 2013(Hu et al, , 2017Xie et al, 2015). If other forms of PC lesions existed, they were generally accompanied by co-existing pulmonary nodules/masses in our practice (Hu et al, 2017). Therefore, calculating those characteristic lesions may underestimate the prevalence of PC, however, in a mild degree.…”
Section: Case Definitionsmentioning
confidence: 64%
“…When asymptomatic, it may be discovered incidentally on radiological imaging. The most common presentation of PC on chest computed tomography (CT) is pulmonary nodules, both in HIVinfected and in HIV-uninfected patients [7][8][9]. Although the common route of cryptococcal infection was considered to be Cryptococcus inhalation into the lung, it mainly affects the central nervous system, causing fever, headache, and other symptoms, while symptomatic pulmonary infection is uncommon.…”
Section: Introductionmentioning
confidence: 99%
“…A large proportion of the patients tested for serum CrAg in our study presented with respiratory symptoms and demonstrated chest radiographic findings, prompting testing. Pulmonary cryptococcosis is challenging to diagnose given the suboptimal sensitivity of respiratory cultures, nonspecificity of radiologic findings, and uncertainty of low-titer serum CrAg results (15,18,24,25). We found that regardless of culture confirmation or clinical signs of disease, the vast majority of patients in the low-titer group were given antifungal therapy for treatment of cryptococcosis.…”
Section: Discussionmentioning
confidence: 89%